Low Psychosine in Krabbe Disease with Onset in Late Infancy: A Case Report - Camille S. Corre; Dietrich Matern; Joan E. Pellegrino; Carlos A. Saavedra-Matiz; Joseph J. Orsini; Robert Thompson-Stone (International Journal of Neonatal Screening, 2021)
Krabbe disease (KD) is a rare inherited neurodegenerative disorder caused by a deficiency in galactocerebrosidase enzyme activity, which can present in early infancy, requiring an urgent referral for hematopoietic stem cell transplantation, or later in life. Newborn screening (NBS) for KD requires identification and risk-stratification of patients based on laboratory values to predict disease onset in early infancy or later in life. The biomarker psychosine plays a key role in NBS algorithms to ascertain probability of early-onset disease. This report describes a patient who was screened positive for KD in New York State, had a likely pathogenic genotype, and showed markedly reduced enzyme activity but surprisingly low psychosine levels. The patient ultimately developed KD in late infancy, an outcome not clearly predicted by existing NBS algorithms. It remains critical that psychosine levels be evaluated alongside genotype, enzyme activity levels, and the patient’s evolving clinical presentation, ideally in consultation with experts in KD, in order to guide diagnosis and plans for monitoring.